Elevated serum carcinoembryonic antigen level after curative surgery is a prognostic biomarker of stage II-III colorectal cancer. Issue 11 (November 2021) - Sonoda, Hiromichi; Yamada, Takeshi; Matsuda, Akihisa; Ohta, Ryo; Shinji, Seiichi; Yokoyama, Yasuyuki; Takahashi, Goro; Iwai, Takuma; Takeda, Kohki; Ueda, Koji; Kuriyama, Sho; Miyasaka, Toshimitsu; et al.
Abstract: Background: High preoperative carcinoembryonic antigen (CEA) is a well-known risk factor for stage II-III colorectal cancer (CRC); however, in most cases, cancer does not recur. Conversely, postoperative CEA (post-CEA) is occasionally measured, and high post-CEA patients often develop recurrence; however, the clinical significance of post-CEA testing is unknown. The purpose of this study was to determine whether post-CEA elevation might indicate a poor prognosis for stage II-III CRC patients who underwent curative surgery. Patients and methods: 482 patients with pathological stage II-III CRC were included. Univariate and multivariate analyses were performed to evaluate post-CEA levels. Results: Multivariate analysis showed that elevated post-CEA (hazard ratio (HR): 3.14, P < 0.001), pathological lymph node metastasis (pN+), and pathological T4 (pT4) are associated with poor recurrence-free survival (RFS), and that elevated post-CEA (HR: 3.12; P = 0.002), pN+, pT4, age >70, and smoking are independently associated with poor overall survival. Subgroup analysis among stage III patients, in combination with the risk classification of the International Duration Evaluation of Adjuvant Chemotherapy (IDEA) study, showed that elevated post-CEA is a significant indicator of poor prognosis for RFS in both low-risk (73.8% vs. 21.2%, P < 0.001) and high-risk (49.9% vs. 25.0%, P = 0.04) groups. Conclusions: Post-surgical CEA elevation is independently associated with poor prognosis in stage II-III CRC. Adding post-CEA levels to the IDEA risk classification may provide a more reliable indicator of the need for individualized surveillance and adjuvant chemotherapeutic strategies.